Terms of trade and exchange rate regimes in developing countries - Christian Broda (Federal Reserve Bank of New York, 2002)
Since Friedman (1953), an advantage often attributed to flexible exchange rate regimes over fixed regimes is their ability to insulate more effectively the economy against real shocks. I use a post-Bretton Woods sample (1973-96) of seventy-five developing countries to assess whether the responses of real GDP, real exchange rates, and prices to terms-of-trade shocks differ systematically across exchange rate regimes. I find that responses are significantly different across regimes in a way that supports Friedman's hypothesis. In response to a negative terms-of-trade shock, countries with fixed regimes experience large and significant declines in real GDP, and the real exchange rate depreciates slowly and by means of a fall in prices. Countries with more flexible regimes, by contrast, tend to have small real GDP losses and immediate large real depreciations. The contributions of terms-of-trade disturbances to the actual fluctuation of real GDP, real exchange rates, and prices are also examined.
Keywords: E30; F31; F33; F41; 330; exchange rate regimes; exchange rate flexibility; terms-of-trade shock; Wechselkurssystem; Terms of Trade; Schock; Kaufkraftparität; Preisniveau; Sozialprodukt; Theorie; Entwicklungsländer